The effects of a systematic approach to solve real-life inventive problems in the science classroom - ŞAHİN, FATMA (My University, 2023)
Nowadays, many education programmes claim to evolve according to present and future skills needed for sustainable development, and one of these skills is inventive problem-solving. Systematic-inventive problem solving (SIPS) is a systematic approach to problem-solving derived from engineering, technology, science, mathematics, and general problem-solving principles. This study presents findings from a SIPS-based methodology to enhance inventive problem-solving in school science for the Light topic. SIPS is an approach for innovative solutions with early judgment by exploring the problem\"s world or surroundings. This study was conducted with 78 seventh-grade pupils in Istanbul, Türkiye. Mixed methods were applied to determine the contribution of SIPS to developing their inventive problem-solving and to get their opinions about SIPS. The data were collected through the pre-post Inventive Problem-Test (IP-T), documentation of pupils’ activities, and interviews. Statistical and descriptive analyses revealed that using inventive problem-solving tasks fostered pupils\" inventive-problem solving skills. Also, using SIPS helped pupils solve real-life problems for which they might need information on different topics such as heat-temperature, electrostatics, or pressure. The study suggests that SIPS makes it possible to increase 7th grade pupils\" interest in science, more comprehensive and focused thinking, and their realisation that what they learn at school is useful in everyday life
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyoloji; Eğitim; Social Sciences and Humanities; Psychology; Sociology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, UYGULAMALI; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, APPLIED; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Uygulamalı Psikoloji; Social Sciences & Humanities; Applied Psychology; ASIT; Inventive Problem; Systematic inventive problem solving (SIPS); TRIZ